Identificação do DNA de aranhas do gênero loxosceles por LAMP como método diagnóstico do envenenamento causado por essas aranhas. - Luana Paula Fernandes (2021)
The early detection of poisonings caused by spiders of the genus Loxosceles is still a challenge for public health and for the patient treatment, due to the difficulty of establishing a diagnosis since the spider bite is painless and the injury caused can be mistaken with other conditions. ELISA methods have already been evaluated for the possibility of detecting these poisonings by detecting protein components of the venom. However, these methods require time and equipment that make practical diagnosis impossible for simple clinics. In this work, we use a fast, simple and visual method, the loop-mediated isothermal amplification (LAMP) with the purpose of detecting DNA from Loxosceles spiders in different samples collected (hair, swab and serum) of experimentally envenomed rabbits. Different conditions of time (15, 30 and 60 minutes), concentration of iniciadores and temperature (60, 65, 68 and 71 ° C) were evaluated with two LAMP methodologies. The visual detection method was chosen because it presents a limit of detection 32 times better (0.315 pg) than non-colorimetric approach and 62 times better than traditional PCR. The developed test was able to detect with efficiency, sensitivity (up to 100%) and specificity (100%) the DNA of Loxosceles intermedia in different samples within 72 hours after the poisoning. The detection could be done visually, eliminating the need for visualization by agarose or polyacrylamide gels. For its effortlessness of implementation, speed, sensitivity and specificity, LAMP has great potential for application in DNA detection of the genus Loxosceles spiders which would help in the diagnosis of poisoning caused by these animals.